2019
DOI: 10.1080/0886022x.2019.1590209
|View full text |Cite
|
Sign up to set email alerts
|

Successful transplantation of kidneys from deceased donors with terminal acute kidney injury

Abstract: Background: There are many doubts with regards to accepting deceased kidneys with acute kidney injury (AKI) for transplantation. Purpose: The aim of this study was to present the 5-years outcome of kidney transplantation cases where deceased donors developed AKI before organ procurement. Methods: Two hundred twenty-six deceased renal transplants were analyzed. Data regarding donors and recipients were collected. Terminal AKI was defined as terminal ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…This finding reflects the association between the severity of acute kidney injury in the donor and DGF recovery time. Retrospective studies identified an association between increased donor final serum creatinine level and an increased risk of DGF [29,30], but failed to identify an association with prolonged DGF duration among recipients with DGF [17]. Dominguez et al [24] also investigated risk factors of prolonged DGF duration, and did not find an association with donor kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…This finding reflects the association between the severity of acute kidney injury in the donor and DGF recovery time. Retrospective studies identified an association between increased donor final serum creatinine level and an increased risk of DGF [29,30], but failed to identify an association with prolonged DGF duration among recipients with DGF [17]. Dominguez et al [24] also investigated risk factors of prolonged DGF duration, and did not find an association with donor kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…DGF is a risk factor for the development of early acute rejection 17,22 . However, previous studies reported that the acute rejection rate was not signi cantly higher among patients whose donors had AKI than among other KT recipients 7,8,10,15 . We also observed that donor AKI did not affect the acute rejection rate or rejection-free survival.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies showed that donors with AKI were associated with a higher rate of DGF 7,8,10,15 , and that the DGF rate was higher with AKIN stage 2 and 3 disease 9,16 . Similarly in our study, the DGF rate tended to increase with the donor AKI stage, especially in stage 3.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the aforementioned uncertainty, terminal donor creatinine has long been thought of as a negative indicator of posttransplant function. Studies have shown higher rates of delayed graft function and prolonged index hospital admission 6‐9 . These studies have, however, used varying absolute serum creatinine levels to stratify between the presence and severity of AKI.…”
Section: Introductionmentioning
confidence: 99%